(untitled) (Quinto Sol, 2019)
In 1786, a count of the inhabitants of the Indian towns of Tucumán was carried out to register the tributaries. This operation was repeated in 1807 and, on that occasion, the visitor noticed that many men from Santiago’s jurisdiction had moved to Buenos Aires to work in the wheat harvest. From both registers, two questions from the same process will be analyzed: the history of these migrants and that of their families of provenance who were awaiting their return.